PAHs in drinking water and contamination source of it - Jonida Canaj; Kozeta Vaso (Zaštita Materijala)
Polycyclic aromatic hydrocarbons (PAHs) are ubiquitous in the environment and are part of numerous organic contaminants that are persistent in the environment. This study was undertaken to assess the identification and concentration of 15 PAHs in drinking water in different geographic regions of Albania. Another purpose is to explain the exposure of them to human health. There are thousands of PAH compounds in the environment but in practice PAH analysis is restricted to a few compounds as: Naphthalene, Acenaphthylene, Acenaphthene, Fluorene, Phenanthrene, Anthracene, Fluoranthene, etc listed by US EPA as potentially toxic. This article describes a reproducible method according to EN ISO 17993:2003 for sample preparation and HPLC analysis of PAHs in water, fluorescence detection mode after liquid-liquid extraction for the determination of 15 selected PAH in drinking and ground water. All the results of the water samples are negative, it is not possible to detect these compounds.